Influence of Herbal Early Chick Nutritional Supplement on the Growth Performance, Serum Biochemicals and Immune Response of Broiler Chicken - Kadam, A.S.; Nikam, M.G.; Patodkar, V.R.; Muglikar, D.M.; Lonkar, V.D.; Yadav, G.B.; Maini, S.; Ravikanth, K.; Meshram, M.D. (International Journal of Poultry Science, 2009)
The experiment was conducted on 150 day-old straight-run “Vencob” broiler chicks for a period of 6 weeks. Day old chicks were randomly divided into three groups I, II and III to evaluate effect of early chick nutritional polyherbal supplement AV/NNC/17 (supplied by Ayurvet Ltd. Baddi, India) on the performance of broilers. The control group I was given basal diet 48 h after hatch. The group II and III were treated with 6 g and 8 g of AV/NNC /17 paste per chick immediately after hatching during transportation period/day till 48 h and then switched over basal diet up to the age of marketing. The overall results of the study indicated that the early chick nutritional supplement AV/NNC/17 @ 6g and 8 g/chick has significant effect upon early growth, gain in weekly weight, feed efficiency and carcass traits between treatment and control indicating an overall beneficial effect of polyherbal product in initial 48 hours of life. In addition to these parameters, immune response, intestinal morphogenesis, intestinal development and gut health are also recorded to improve significantly in treatment groups.